2017
DOI: 10.1108/jmlc-07-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Tracking digital footprints: anonymity within the bitcoin system

Abstract: Purpose The purpose of this paper is to critically analyse research surrounding the anonymity of online transactions using Bitcoin and report on the feasibility of law enforcement bodies tracing illicit transactions back to a user’s real-life identity. Design/methodology/approach The design of this paper follows on from the approach taken by Reid and Harrigan (2013) in determining whether identifying information may be collated with external sources of data to identify individual users. In addition to conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Indeed, all bitcoin transactions are stored publicly and permanently on the network. The bitcoin system presented in these terms is not a tool of anonymity, but rather a transparent and trackable means of information shared across a network that does not rely on a centralized agency [34]. However, this is true in principle because it can be used anonymously by applying a bitcoin address once.…”
Section: Social Aspects Of Sustainabilitymentioning
confidence: 99%
“…Indeed, all bitcoin transactions are stored publicly and permanently on the network. The bitcoin system presented in these terms is not a tool of anonymity, but rather a transparent and trackable means of information shared across a network that does not rely on a centralized agency [34]. However, this is true in principle because it can be used anonymously by applying a bitcoin address once.…”
Section: Social Aspects Of Sustainabilitymentioning
confidence: 99%
“…
1A1zP1eP5QGefi2DMPTfTL5SLmv7DivfNa These pseudonymous addresses, such as the one above, do not in fact provide an absolute level of anonymity, and there are several techniques that can be used to identify the owner of such an address. Web (HTTP) cookies (Goldfelder et al, ), IP addresses (Koshy et al, ), clustering techniques – where several bitcoin addresses can be identified as being controlled by one user (Meiklejohn et al, ) – information provided by users to cryptocurrency exchanges when they sign up (Reynolds & Irwin, ), as well as the public disclosure of addresses on social media (Reid & Harrigan, ), are all ways in which these pseudonymous addresses can be traced back to their owner. For instance, law enforcement agencies have been able to trace transactions as part of investigations into illicit activity; during investigations into the Silk Road Marketplace – the online marketplace where users could purchase illicit drugs and other goods using bitcoin – the FBI were able to track the provenance of over 700,000 bitcoin and connect individuals to illegal activities (Greenberg, ).
…”
Section: Fungibility Privacy and Private Currenciesmentioning
confidence: 99%
“…This can be mitigated through designing alternate cryptocurrency called Scrooge-Coin (Chiu & Koeppl, 2017). (Reynolds & Irwin, 2017) Found that to keep up with a rapidly expanding global environment, and with the gap between the 'global' and the 'local' becoming smaller, criminals are adopting new forms of currency, such as cryptocurrency, to increase the level of anonymity afforded to their illicit activities. Further, the compliance and implementation of anti-money laundering legislation and customer identification security standards are insufficiently utilized within some exchange services, resulting in more technologically adept, or well-funded, criminals being able to circumvent identification controls and continue to transact without revealing their identities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The notable fact about the currency is it do not require banks to process payments (Grinberg, 2011) and is self-regulatorynot requiring any central regulatory authority (Reynolds & Irwin, 2017).…”
Section: Introductionmentioning
confidence: 99%